If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (u + -1)(u + -3) = 48 Reorder the terms: (-1 + u)(u + -3) = 48 Reorder the terms: (-1 + u)(-3 + u) = 48 Multiply (-1 + u) * (-3 + u) (-1(-3 + u) + u(-3 + u)) = 48 ((-3 * -1 + u * -1) + u(-3 + u)) = 48 ((3 + -1u) + u(-3 + u)) = 48 (3 + -1u + (-3 * u + u * u)) = 48 (3 + -1u + (-3u + u2)) = 48 Combine like terms: -1u + -3u = -4u (3 + -4u + u2) = 48 Solving 3 + -4u + u2 = 48 Solving for variable 'u'. Reorder the terms: 3 + -48 + -4u + u2 = 48 + -48 Combine like terms: 3 + -48 = -45 -45 + -4u + u2 = 48 + -48 Combine like terms: 48 + -48 = 0 -45 + -4u + u2 = 0 Factor a trinomial. (-5 + -1u)(9 + -1u) = 0Subproblem 1
Set the factor '(-5 + -1u)' equal to zero and attempt to solve: Simplifying -5 + -1u = 0 Solving -5 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1u = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1u = 0 + 5 -1u = 0 + 5 Combine like terms: 0 + 5 = 5 -1u = 5 Divide each side by '-1'. u = -5 Simplifying u = -5Subproblem 2
Set the factor '(9 + -1u)' equal to zero and attempt to solve: Simplifying 9 + -1u = 0 Solving 9 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1u = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1u = 0 + -9 -1u = 0 + -9 Combine like terms: 0 + -9 = -9 -1u = -9 Divide each side by '-1'. u = 9 Simplifying u = 9Solution
u = {-5, 9}
| 8x+5x+4+8=8x+4+4x | | 12+5y=2y-9 | | 2-3a/4=5 | | a^2=-9a | | -7(5r+1)+5r=-6r+6(-4r+3) | | 28/20=x/9 | | 5y+6=y^2 | | -7(5r+1)+5r=-6+6(-4r+3) | | -a+10=2a-8 | | 6(6r+6)=108 | | 20.00-1.45h=1.15 | | 4x+5+x^2+10=180 | | p(p-13)=-22 | | 8n-5(n+1)=-5(1-4n) | | 4x+5+x^2+10=180-y^2 | | p^2=9p-20 | | 10z^3+11z^2+3z=0 | | 4x+5=y^2 | | y=1.3x+1.3 | | 3(8-4r)=8(r-7) | | 4a-4=2a+14 | | 9w-21=3(w-7)+6w | | 2(5x+6)=10x+23 | | 10y^2-11y-6=0 | | 2(1+3n)=4(3+2n) | | 15y^2+1y-6=0 | | 8x-(4x+3)=29 | | -2=-3x | | 2(v-8)-5v=-10 | | -84=6(3n-5) | | 12-3x=21 | | -(8y+4)-(-7-5)=-2 |